Financial systems in financial crisis: An analysis of banking systems in the EU - Daniel Detzer; Jérôme Creel; Fabien Labondance; Sandrine Levasseur; Mimoza Shabani; Jan Toporowski; Judith Tyson; Costanza Consolandi; Giampaolo Gabbi; Massimo Matthias; Pietro Vozzella; Carlos A. Carrasco; et al. (Intereconomics, 2014)
This Forum aims to systematically describe and analyse the evolution of national financial systems within the EU over the past three decades. It analyses the processes of financialisation that have dominated this period as well as the causes and consequences of the financial crisis from the perspectives of five individual member states: Germany, France, the UK, Italy and Spain. Furthermore, policy proposals which could change the role of the financial system to better serve economic and social objectives are also put forward.
Keywords: 330; Finanzsektor; Bankgeschäft; Finanzkrise; Finanzmarktregulierung; Geschichte; Deutschland; Frankreich; Großbritannien; Italien; Spanien